Intra- and inter-observer agreement and reliability of bone mineral density measurements around acetabular cup: a porcine ex-vivo study using single- and dual-energy computed tomography. (July 2017) - Mussmann, Bo; Overgaard, Søren; Torfing, Trine; Bøgehøj, Morten; Gerke, Oke; Andersen, Poul Erik
Background: Periprosthetic bone loss is considered to be a potentially contributing factor in aseptic loosening of acetabular hip components, but no studies have shown this association. The lack of association might be caused by insufficient image quality because of metal artifacts and challenges in measuring bone density (BMD) in complex anatomic structures which might be overcome using dual-energy computed tomography (DECT). Purpose: To test inter- and intra-observer agreement and reliability of in-house segmentation software measuring BMD adjacent to acetabular cup and to compare measurements performed with single-energy CT (SECT) and DECT in cemented and cementless cups. Material and Methods: Twenty-four acetabular cups inserted in porcine hip specimens were scanned with SECT and DECT. Bone density was measured in a three-dimensional volume adjacent to the cup. Double measurements were performed. Results: BMD derived from SECT was approximately four times higher than that of DECT. In both scan modes, intraclass correlation coefficient (ICC) was >0.90 with no differences between repeated measurements, except for uncemented cups where a statistically significant difference of 11 mg/cm 3 was found with DECT. DECT showed narrower limits of agreement than SECT. Inter-observer analysis showed small differences. Conclusion: BMD can be estimated with high intra- and inter-observer reliability with SECT and DECT around acetabular cups using custom software. The intra- and inter-observer agreement of DECT is superior to that of SECT and better in the cementless concept. Good intra- and inter-observer reliability can be obtained in both cemented and cementless cups using the segmentation software. SECT and DECT cannot be used interchangeably.